2000
DOI: 10.2214/ajr.175.3.1750829
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging of the Salivary Glands in Sicca Syndrome

Abstract: Our findings suggest a distinct entity of sicca syndrome in patients with hyperlipidemia compared with patients with Sjögren's syndrome. Characteristic MR imaging findings of salivary glands in patients with hyperlipidemia included extensive lipid infiltration and gland enlargement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…In addition, Izumi et al suggest that parotid gland is more affected by hyperlipidemia than submandibular gland [16, 17]. The above results are in accordance with the findings of Sheikh et al, suggesting a close relationship between parotid gland swelling and high levels of triglycerides in plasma [10, 16, 17]. …”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…In addition, Izumi et al suggest that parotid gland is more affected by hyperlipidemia than submandibular gland [16, 17]. The above results are in accordance with the findings of Sheikh et al, suggesting a close relationship between parotid gland swelling and high levels of triglycerides in plasma [10, 16, 17]. …”
Section: Resultssupporting
confidence: 84%
“…According to the biochemical data hyperlipidemic diet leads to an elevated serum lipid profile that might be responsible for parotid gland swelling as it is referred from Goldman and Julian, Kaltreider and Talal, Manganelli et al, and Tretbar [3, 4, 6, 19]. In addition, Izumi et al suggest that parotid gland is more affected by hyperlipidemia than submandibular gland [16, 17]. The above results are in accordance with the findings of Sheikh et al, suggesting a close relationship between parotid gland swelling and high levels of triglycerides in plasma [10, 16, 17].…”
Section: Resultsmentioning
confidence: 99%
“…Lipid infiltration was rarely observed in salivary glands from patients with primary SS. The authors concluded that clinical features, functional studies, specific imaging features of the parotid gland and histopathologic features of patients with a sicca syndrome related to dyslipidemia were clearly different from those found in patients with primary SS [91].…”
Section: Dyslipidemiamentioning
confidence: 94%
“…The frequency of xerostomia was only specified by Kaltreider and Talal [89] who found that only one out of the five patients with parotidomegaly related to dyslipidemia presented xerostomia, suggesting that xerostomia and parotid swelling do not always coincide. However, later experimental studies supported the possible role of lipid abnormalities in the etiopathogenesis of primary SS [91][92][93].…”
Section: Dyslipidemiamentioning
confidence: 99%
See 1 more Smart Citation